Substituting hospital-based outpatient cardiology care: The impact on quality, health and costs - Quanjel, Tessa C. C. (PLoS One, 2019)
BACKGROUND: Many Western countries face the challenge of providing high-quality care while keeping the healthcare system accessible and affordable. In an attempt to deal with this challenge a new healthcare delivery model called primary care plus (PC+) was introduced in the Netherlands. Within the PC+ model, medical specialists perform consultations in a primary care setting. PC+ aims to support the general practitioners in gatekeeping and prevent unnecessary referrals to hospital care. The aim of this study was to examine the effects of a cardiology PC+ intervention on the Triple Aim outcomes, which were operationalized by patient-perceived quality of care, health-related quality of life (HRQoL) outcomes, and healthcare costs per patient. METHODS: This is a quantitative study with a longitudinal observational design. The study population consisted of patients, with non-acute and low-complexity cardiology-related health complaints, who were referred to the PC+ centre (intervention group) or hospital-based outpatient care (control group; care-as-usual). Patient-perceived quality of care and HRQoL (EQ-5D-5L, EQ-VAS and SF-12) were measured through questionnaires at three different time points. Healthcare costs per patient were obtained from administrative healthcare data and patients were followed for nine months. Chi-square tests, independent t-tests and multilevel linear models were used to analyse the data. RESULTS: The patient-perceived quality of care was significantly higher within the intervention group for 26 out of 27 items. HRQoL outcomes did significantly increase in both groups (P <0.05) but there was no significant interaction between group and time. At baseline and also at three, six and nine months’ follow-up the healthcare costs per patient were significantly lower for patients in the intervention group (P<0.001). CONCLUSIONS: While this study showed no improvements on HRQoL outcomes, PC+ seemed to be promising as it results in improved quality of care as experienced by patients and lower healthcare costs per patient.